Brain death in low-income countries: a report from Malawi. (April 2019) - Prin, Meghan; Quinsey, Caroline; Kadyaudzu, Clement; Hadar, Eldad; Charles, Anthony
Most low-income nations have no practice guidelines for brain death; data describing brain death in these regions is absent. Our retrospective study describes the prevalence of brain death among patients treated in an intensive care unit (ICU) at a referral hospital in Malawi. The primary outcome was designation of brain death in the medical chart. Of 449 ICU patients included for analysis between September 2016 and May 2018, 43 (9.6%) were diagnosed with brain death during the ICU admission. The most common diagnostic reasons for admission among these patients were trauma (49%), malaria (16%) and postoperative monitoring after general abdominal surgery (19%). All patients diagnosed with brain death were declared dead in the hospital, after cardiac death. In conclusion, the incidence of brain death in a Malawi ICU is substantially higher than that seen in high-income ICU settings. Brain death is not treated as clinical death in Malawi.